The multilateralism of the new development bank on the sustainable economic growth in BRICS nations and beyond - Tshikovhi, Ndivhuho; Netswera, Fulufhelo; Zhu, Jiejin (Emerald Publishing Limited, 2025)
Founded in 2015 as an alternative to the World Bank, the BRICS New Development Bank (NDB) offers vital financial resources for its member nations and supports development in emerging and developing economies. The Multilateralism of the New Development Bank on the Sustainable Economic Growth in BRICS Nations and Beyond brings together diverse perspectives to assess the NDB's effectiveness and its role in promoting global sustainability. It examines the BRICS Multilateral Cooperation and Co-Financing Agreement for Sustainable Development, highlighting projects focused on climate change mitigation, sustainable infrastructure, renewable energy, and the preservation of natural resources. Suitable for bankers, development analysts, policymakers, NGOs and students, this book offers crucial insights into the evolving landscape of global development finance.
Includes index.
Keywords: Economic development.; Business & Economics -- Development -- Economic Development.; Development economics and emerging economies.; elektronické knihy; electronic books